2020
DOI: 10.1109/access.2020.2971221
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Mechanical Characteristics via Kinematic Wave Model for Snake-Like Robot Executing Exploration of Lunar Craters

Abstract: It is extremely difficult to collect deep lunar soil samples during lunar exploration, as the average thickness of lunar soils is very large, and the power of lunar soil sampling systems is inherently limited. In this paper, we propose the use of serpentine robots to explore lunar craters. Our approach is to first design a kinematic wave model that allows the serpentine robot to satisfy all the requirements of lunar exploration. The resistance encountered by each part of the robot during its motions was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[50][51][52] As shown in Figure 11, the application prospects of 3D printed dielectric elastomers or dielectric elastomer actuators are broad. The production printed by 3D printers can be used in the deep sea, planetary surfaces, 57 narrow confined spaces, high-voltage cables, 58 and other unstructured environments. Soft robots with modular structures have shown great advantages in industry, medical field, 59 post-disaster search and rescue fields.…”
Section: D Printing Of Dielectric Elastomer Actuatorsmentioning
confidence: 99%
“…[50][51][52] As shown in Figure 11, the application prospects of 3D printed dielectric elastomers or dielectric elastomer actuators are broad. The production printed by 3D printers can be used in the deep sea, planetary surfaces, 57 narrow confined spaces, high-voltage cables, 58 and other unstructured environments. Soft robots with modular structures have shown great advantages in industry, medical field, 59 post-disaster search and rescue fields.…”
Section: D Printing Of Dielectric Elastomer Actuatorsmentioning
confidence: 99%
“…The snake-inspired robots as a continuum robot (Wei et al , 2020) have reconfigurable modular structural units and unique merits in using its whole body’s flexible deformation for locomotion and grasping. Therefore, it can also be used in the deep sea (Ludvigsen and Sørensen, 2016), planetary surface (Hou et al , 2020; Liu et al , 2016), narrow confined spaces (Brunete et al , 2012), high-voltage cables (Wei et al , 2014; Yang et al , 2021) and other unstructured environments. Meanwhile, snake-inspired robots with modular structures and multiple gaits (Wang et al , 2017) have shown great advantages in industrial field, military field, medical field and post-disaster search and rescue fields (Jin et al , 2019; Zhang and Lu, 2020).…”
Section: Application Prospectmentioning
confidence: 99%
“…The finite element model is saved as modal neutral file and imported into ADAMS to form a flexible body, and the rigid flexible coupling model of plow is formed [35], [36]. The data transmission between EDEM software and ADAMS software can be realized by EALink add-on, and the EDEM -ADAMS collaborative simulation platform is established [37]. The stress distribution of plow bit is obtained by the bidirectional coupling calculation between EDEM and ADAMS, as shown in Fig.…”
Section: Stress Analysis Of Plow Bitmentioning
confidence: 99%